Glucose-conjugated platinum(IV) complexes as tumor-targeting agents: design, synthesis and biological evaluation - Wang, Haifeng; Yang, Xiande; Zhao, Caili; Wang, Peng George; Wang, Xin (Bioorganic & medicinal chemistry, 2019)
[Display omitted] A new series of glucose-conjugated Pt(IV) complexes that target tumor-specific glucose transporters (GLUTs) was designed, synthesized, and evaluated for their anticancer activities. All six compounds, namely, A1-A6, exhibited increased cytotoxicity that were almost six fold higher than that of oxaliplatin to MCF-7 cells. These Pt(IV) complexes can be reduced to release Pt(II) complexes and cause the death of tumor cells. Simultaneously, the glycosylated Pt(IV) complexes (30.21–91.33 μM) showed lower cytotoxicity that normal LO2 cells compared with cisplatin (5.25 μM) and oxaliplatin (8.34 μM). The intervention of phlorizin as a GLUTs inhibitor increased the IC50 value of the glycosylated Pt(IV) complexes, thereby indicating the potential GLUT transportability. The introduction of glucose moiety to Pt(IV) complexes can effectively enhance the Pt cellular uptake and DNA platination. Results suggested glucose-conjugated Pt(IV) complexes had potential for further study as new anticancer agents.